Uncovering Human Tooth Marks in the Search for Dog Domestication: The Case of Coímbre Cave - Idoia Claver; Verónica Estaca; María de Andrés-Herrero; Darío Herranz-Rodrigo; David Álvarez-Alonso; José Yravedra (Animals)
The domestication of the dog (Canis lupus familiaris) is one of the oldest and most complex processes of interaction between humans and animals. This phenomenon may have begun sometime between 30 and 15 ky calBP. Archaeological and genetic studies have provided valuable insights into dog domestication, although the precise geographic location and origin of this process remain controversial and under debate. New methodologies, such as taphonomic analyses, offer opportunities to deepen our understanding of past human–dog interactions. In this context, the present study examines tooth marks found on some bone remains from the Upper Magdalenian site (15,500–13,200 cal BP) of Coímbre Cave (Peñamellera Alta, Asturias, Spain). The low incidence of carnivores at the site has raised the possibility that the tooth marks may have been produced by canids. However, a detailed taphonomic analysis combining geometric morphometrics with robust statistical methods—including MANOVA with post-hoc permutation tests—revealed that the marks identified at the site do not significantly differ from tooth marks produced by humans (p = 0.086). In contrast, tooth marks produced by other carnivores, such as Canis lupus signatus and Canis lupus familiaris, showed significant differences (p < 0.003). Although our study could not confirm the presence of domesticated dogs at the Magdalenian levels of Coímbre Cave, it has documented taphonomic processes that are rarely identified in the archaeological record. Furthermore, this study highlights the potential of tooth mark analysis as a key tool for future research on human–animal interactions in archaeological contexts.